The Evaluation of Nodal Tumor Volume in Nasopharyngeal Carcinoma - Yıldırım, Halil Cumhur; Kanat, Sevda; Akovalı, Emine Sedef; Dağdelen, Meltem; Çavdar Karaçam, Songül; Uzel, Ömer (Cerrahpaşa Medical Journal, 2023)
Objective: The aim of this study is to evaluate the value of nodal tumor volume in predicting distant metastasis in nasopharyngeal carcinoma and to investigate the feasibility of nodal tumor volume-guided patient selection for induction chemotherapy. Methods: Eighty-eight patients with nasopharyngeal carcinoma treated with intensity-modulated radiotherapy ± chemotherapy between 2010 and 2016 were reviewed. Nodal tumor volume was calculated in radiotherapy planning computed tomography fused with the initial magnetic resonance imaging and positron emission tomography and computed tomography. Survival analysis was made by the Kaplan–Meier method. Results: Median follow-up time for surviving patients was 76 months. Sixteen (18.2%) patients developed distant metastasis. Nine (10.2%) patients developed locoregional recurrence. Five-year overall survival, locoregional recurrence-free survival, and metastasis-free survival rates were 71.5%, 87%, and 79.4%, respectively. In multivariate analysis, nodal tumor volume > 45 cc [hazard ratio: 7.160 (95% CI: 2.560-20.024), P < .001] and advanced T stage [hazard ratio: 3.419 (95% CI: 1.238-9.442), P = .018] were found as predictive parameters for metastasis-free survival, whereas only age ≥50 [hazard ratio: 2.939 (95% CI: 1.182-7.308), P = .020] was found to be a negative independent factor of overall survival. Conclusion: Nodal tumor burden has a predictive role for distant metastasis in nasopharyngeal carcinoma. Patients with nodal tumor volume > 45 cc have worse metastasis-free survival than patients with nodal tumor volume ≤ 45 cc. Consideration of nodal tumor volume may increase the accuracy of patient selection to escalate systemic therapy. Cite this article as: Yıldırım HC, Kanat S, Akovalı ES, Dağdelen M, Çavdar Karaçam S, Uzel Ö. The role of nodal tumor volume in nasopharyngeal carcinoma. Cerrahpaşa Med J. 2023;47(2):150-155.